Kontribusi Pendapatan Usahatani Jagung terhadap Pendapatan Usahatani di Desa Aek Ulok Kecamatan Habinsaran Kabupaten Toba - LUBIS, EYEN MERIAH; DEWI, RATNA KOMALA; BUDIASA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Contribution of Corn Farming Income to Farm Income in Aek Ulok Village, Habinsaran District, Toba Regency.  Corn is one of the agricultural commodities that is commonly found in Aek Ulok Village, Habinsaran District, Toba Regency. This study aims to determinate the farmers income from corn farming and analyze the contribution of farmers income from corn farming to farm income in Aek Ulok Village. The sampling technique used was method ramdom sampling and the samples taken randomly with 30 corn farmers.  The data collection was conducted from early February to the end of February 2022. The results showed that the income of farmers from corn farming with an average planting area of ??0.85 ha was Rp 32.056.500.00/year/respondent and contributed 61.57% of the total farm income, which shows that maize farming in Aek Ulok Village provides a large contribution to farmers' income. Corn farmers in Aek Ulok Village need to maximize the use of labor in the family considering that labor costs are the highest costs incurred by farmers in corn farming.